Sensory Behaviours and Resting Parasympathetic Functions among Children with and without ADHD - Ivan Neil Gomez; Lissa Martha Domondon; Hector WH Tsang; Chetwyn CH Chan; Cynthia YY Lai (The Scientific World Journal)
Previous studies suggest that parasympathetic functions support sensory behaviours. However, the relationship between sensory behaviours and parasympathetic functions remain inconclusive and inconsistent among children with and without attention-deficit hyperactivity disorder (ADHD). This research aims to examine the sensory behaviours and resting parasympathetic functions among children with and without ADHD. We compared sensory behaviours and baseline parasympathetic functions of 64 participants, with 42 typically developing and 24 ADHD male children aged 7–12 years. Sensory behaviours were evaluated using the sensory profile. Baseline parasympathetic functions were indexed using the normalized unit of heart rate variability high-frequency bands (HF n.u.). Children underwent an experimental protocol consisting of watching a silent cartoon movie while HF n.u. is continuously monitored, within a controlled environment. The results of this research showed significantly lower HF n.u. (t(64) = 7.84, p<0.01) and sensory processing total score (t(64) = 14.13 = p<0.01) among children with ADHD compared to their typically developing peers. Likewise, a significant moderate positive correlation (r = 0.36, p<0.05) was found between the HF n.u. and sensory profile total scores among children with ADHD. Children with ADHD have significantly lower resting state parasympathetic functions compared to their typically developing peers.